Lymphoepithelial Cyst of the Mediastinum - Ulku, Refik (2005)
We report a rare case of lymphoepithelial cyst of the mediastinum. A 38-year-old woman was found to have a right paratracheal mediastinal mass on chest radiograph. Computed tomographic scanning showed a cystic mass on the right side of the trachea. The encapsulated mass was situated in the upper mediastinum and was adherent to the trachea. The lesion was resected via a right thoracotomy. Histopathologic examination showed that the cystic mass was lined with 1 layer of ciliate columnar epithelium. There were no malignant foci. These findings were consistent with a diagnosis of multicystic lymphoepithelial cyst. The postoperative course was uneventful, and the patient was discharged from the hospital on the 7th postoperative day.